Giant uterine arteriovenous malformation. A case report - Lacunza Paredes, Rommel Omar (2021)
The case of a patient who presented with abnormal uterine hemorrhage due to an acquired arteriovenous malformation diagnosed with Doppler ultrasound and magnetic resonance is presented. This pathology is becoming more and more frequent and with serious consequences, if proper and timely management is not given.